Companion to Greek tragedy - Gregory, Justina (Blackwell companions to the Ancient World (Online), 2007)
Focusing on Greek tragedy, this book introduces the various methodologies and the critical dialogue that characterize the study of Greek tragedy. Containing 31 essays divided into four sections, it includes ancient Greek transliterated and translated, and technical terms are explained as they appear.